2018
DOI: 10.1016/j.adolescence.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Personal and perceived public mental‐health stigma as predictors of help‐seeking intentions in adolescents

Abstract: This study aimed to determine predictors of help-seeking intentions for symptoms of depression/ anxiety and self-harm in adolescents. It focused on personal and perceived public stigma to gather data of value for the design of anti-stigma interventions. Participants (n = 722; 368 girls) were recruited from three cohorts of secondary school students in Ireland (mean ages: 1st = 12.9 years; 3rd = 14.9 years; 5th = 16.6 years). Hierarchical regression models indicated that perceived public stigma is a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 45 publications
5
78
0
1
Order By: Relevance
“…For example, Vogel et al (2007) have shown that the effect of public stigma on the utilization of mental health services operates through self-stigma. Nearchou et al (2018) find that help-seeking intentions in adolescents are more affected by public stigma beliefs than their personal stigma beliefs.…”
Section: The Role Of Cultural Stigma Beliefs: Theoretical Reasoningmentioning
confidence: 75%
See 2 more Smart Citations
“…For example, Vogel et al (2007) have shown that the effect of public stigma on the utilization of mental health services operates through self-stigma. Nearchou et al (2018) find that help-seeking intentions in adolescents are more affected by public stigma beliefs than their personal stigma beliefs.…”
Section: The Role Of Cultural Stigma Beliefs: Theoretical Reasoningmentioning
confidence: 75%
“…In contrast to the aforementioned studies, we do not conceptualize cultural stigma beliefs as individual perceptions of what the "generalized other, " or "most people" believe (Pattyn et al, 2014), nor do we approach them as the perceived attitudes, beliefs, and behavioral dispositions of the general population, which are often referred to as "public stigma" (Corrigan and Shapiro, 2010;Pescosolido, 2013;Nearchou et al, 2018). The cross-national, multi-level design of our study allows us to draw a distinction between the prevailing stigma beliefs within a country and the beliefs of individuals by aggregating individuals' beliefs at the country level.…”
Section: The Role Of Cultural Stigma Beliefs: Theoretical Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, younger adolescents had greater knowledge about professional sources of help [34]. Only one study found a significant difference between ages regarding help-seeking, with younger adolescents reporting higher intentions of seeking help [60].…”
Section: Secondary Outcomementioning
confidence: 96%
“…Seven studies did not find significant differences between genders [28-39-40-42-46-51-69]. One study reported higher help-seeking intentions in males experiencing suicidal intentions [60] and two studies found that females perceived more overall barriers . However, this may be related to higher rates of females seeking help for mental health problems compared to males [31-33-37-42-48-53-58-61-76].…”
Section: Secondary Outcomementioning
confidence: 99%